Social dialogue and social partnership: similar and peculiar - Iryna Shavkun; Yana Dybchynska (Менеджмент та підприємництво: тренди розвитку)
The importance of a comparative study of social partnership and social dialogue arises from several key factors. In today's society, the regulation of labor relations, the protection of workers' rights, and the maintenance of social stability are critical issues. Both social partnership and social dialogue play a vital role in facilitating agreements between the state, employers, and employees.